PEMBERIAN EDUKASI DAN TEKNIK RELAKSASI PROGRESIF TERHADAP TINGKAT KECEMASAN PASIEN INFARK MIOCARD DI RSUD DR. PIRNGADI MEDAN TAHUN 2022 - DANIEL SURANTA GINTING; Rini Debora Silalahi; Joko Sutejo; Zuliawati Zuliawati; Friska Ernita Sitorus (INSTITUT KESEHATAN DELI HUSADA, 2022)
Acute Myocardial Infarction (AMI) also known as cardiac arrest, coronary occlusion, or simply coronary, is a life-threatening condition characterized by the formation of localized necrotic areas within the myocardium. Anxiety is the strongest predictor of disease. To reduce one's anxiety, it is necessary to have the ability to accept a process of change. A person in a conscious and not anxious state is able to make someone accept what is experienced. Acceptance will make a good psychological change, so good acceptance will make a positive change of mind. One that is very influential on the psychological state of patients with heart disorders so that they will be able to change the patient's coping patterns in dealing with illness and living their lives is the emergence of anxiety. All clients are prone to feelings of anxiety when they seek help with health problems. Easy and appropriate nursing interventions are needed in AMI patients to help reduce anxiety in supporting patient recovery. Community service providing education and progressive relaxation techniques to the level of anxiety of myocardial infarction patients are patients who are treated at RSUD Dr. Pirngadi Medan. Anxiety is closely related to feelings of uncertainty and helplessness, this emotional state has no specific object. Anxiety is different from fear. From the analysis of five articles on independent nursing interventions to reduce anxiety in AMI patients, it is concluded that aromatherapy interventions are very effective in helping reduce anxiety in AMI patients. The results of the study can be considered nursing interventions to reduce anxiety in AMI patients by providing education and progressive relaxation techniques